Sindbis Virus Replicon-Based SARS-CoV-2 and Dengue Combined Vaccine Candidates Elicit Immune Responses and Provide Protective Immunity in Mice - Yihan Zhu; Wenfeng He; Rui Hu; Xiahua Liu; Mengzhu Li; Yuan Liu (Vaccines)
Background/Objectives: Since its emergence in 2019, the rapid spread of SARS-CoV-2 led to the global pandemic. Recent large-scale dengue fever outbreaks overlapped with the COVID-19 pandemic, leading to increased cases of co-infection and posing severe public health risks. Accordingly, the development of effective combined SARS-CoV-2 and dengue virus (DENV) vaccines is necessary to control the spread and prevalence of both viruses. Methods: In this study, we designed Sindbis virus (SINV) replicon-based SARS-CoV-2 and DENV chimeric vaccines using two delivery strategies: DNA-launched self-replicating RNA replicon (DREP) and viral replicon particle (VRP) systems. Results: Cellular and animal experiments confirmed that the vaccines effectively produced viral proteins and elicited strong immunogenicity. These vaccines induced robust immune responses and neutralizing activity against live SARS-CoV-2, DENV1, and DENV2 viruses. In addition, passively transferred sera from BALB/c mice immunized with these vaccines into AG129 mice provided significant protection against lethal DENV2 challenge. The transferred sera protected the mice from physical symptoms, reduced viral loads in the kidney, spleen, liver, and intestine, and prevented DENV2-induced vascular leakage in these tissues. Conclusions: Therefore, combined vaccines based on the SINV replicon system are promising candidates for pandemic control. These results lay a foundation for further development of a safe and effective combination vaccine against SARS-CoV-2 and DENV.